2009
DOI: 10.1158/1078-0432.ccr-08-2188
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiles Associated with Early Micrometastasis in Lung Cancer: Relevance of 4q Deletion

Abstract: Purpose: Bone marrow is a common homing organ for early disseminated tumor cells (DTC) and their presence can predict the subsequent occurrence of overt metastasis and survival in lung cancer. It is still unclear whether the shedding of DTC from the primary tumor is a random process or a selective release driven by a specific genomic pattern. Experimental Design: DTCs were identified in bone marrow from lung cancer patients by an immunocytochemical cytokeratin assay. Genomic aberrations and expression profiles… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
68
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 37 publications
5
68
1
3
Order By: Relevance
“…Nevertheless, the development of cell lines or xenografts from hundreds of CTCs at the beginning is a major achievement, considering the enormous challenge to establish cell lines from even millions of primary tumor cells. This can be explained by the assumption that viable CTCs might already be selected for better survival and growth properties, which is consistent with published reports demonstrating that tumor cell dissemination and survival of disseminated tumor cells and CTCs is not a random process (34,35 ) and that CTC cell lines and xenografts express cancer stem cell properties (9,11 ). These studies nourish the hope that in-depth functional analysis of CTCs might lead to the identification of metastasisinitiator cells.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, the development of cell lines or xenografts from hundreds of CTCs at the beginning is a major achievement, considering the enormous challenge to establish cell lines from even millions of primary tumor cells. This can be explained by the assumption that viable CTCs might already be selected for better survival and growth properties, which is consistent with published reports demonstrating that tumor cell dissemination and survival of disseminated tumor cells and CTCs is not a random process (34,35 ) and that CTC cell lines and xenografts express cancer stem cell properties (9,11 ). These studies nourish the hope that in-depth functional analysis of CTCs might lead to the identification of metastasisinitiator cells.…”
Section: Discussionsupporting
confidence: 86%
“…An isotype-matched, murine monoclonal antibody (MOPC 21, IgG1; Sigma-Aldrich) served as a negative control. Screening for CK-positive cells was performed in an automated fashion (ACIS system) using color-based imaging technology and microscopy to automatically scan and analyze immunohistochemically stained slides ( 45 ).…”
Section: Bone Marrow Analysismentioning
confidence: 99%
“…Wrage et al 19 reported that the loss of 4q, especially 4q12-q23, in primary lung cancer was significantly associated with bone marrow metastasis. In addition, the same loss was also found to be common in brain metastases from lung cancer patients.…”
Section: Genetic Changesmentioning
confidence: 99%